2017
DOI: 10.1371/journal.pone.0177471
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide survey of B-box proteins in potato (Solanum tuberosum)—Identification, characterization and expression patterns during diurnal cycle, etiolation and de-etiolation

Abstract: Plant B-box domain proteins (BBX) mediate many light-influenced developmental processes including seedling photomorphogenesis, seed germination, shade avoidance and photoperiodic regulation of flowering. Despite the wide range of potential functions, the current knowledge regarding BBX proteins in major crop plants is scarce. In this study, we identify and characterize the StBBX gene family in potato, which is composed of 30 members, with regard to structural properties and expression profiles under diurnal cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 49 publications
2
49
0
Order By: Relevance
“…The BBX TF family has been extensively studied in A. thaliana, whose proteins were classified into five groups accordingly to the domain structure 3,5 . Similar classification was reported for other species such as tomato 36 , potato 51 , rice 52 and grapevine 53 . However, not all provided a phylogeny with high branch support for the groupings and the lack of outgroup led the evolutionary history of the protein family ambiguous.…”
Section: Solanum Lycopersicum Harbours Similar Diversity Of Bbx Protesupporting
confidence: 84%
See 2 more Smart Citations
“…The BBX TF family has been extensively studied in A. thaliana, whose proteins were classified into five groups accordingly to the domain structure 3,5 . Similar classification was reported for other species such as tomato 36 , potato 51 , rice 52 and grapevine 53 . However, not all provided a phylogeny with high branch support for the groupings and the lack of outgroup led the evolutionary history of the protein family ambiguous.…”
Section: Solanum Lycopersicum Harbours Similar Diversity Of Bbx Protesupporting
confidence: 84%
“…These results indicate that tomato BBX genes that belong to structure group IV and V are light responsive, like observed in A. thaliana 4 , and most are light-induced. The expression pattern of BBX encoding genes in Solanum tuberosum during de-etiolation was also addressed and the expression of most of the genes belonging to structural groups IV and V was modulated upon illumination of etiolated leaves 51 . This profile provides further evidences about a link between mRNA levels of BBX proteins from structure groups IV and V and plastid biogenesis and differentiation, revealing that they are affected, to some extent, by the light signalling cascade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous study also found a similar number of BBX genes in the rice genome [14]. The number of BBX gene family members is pretty consistent among different crop plants, such as 30, 32, 29 and 30 BBX genes members were already identified in rice, Arabidopsis , tomato, and potato, respectively [1, 14, 33, 36]. The difference in the number of BBX genes among the crops plants is very less.…”
Section: Discussionmentioning
confidence: 56%
“…BBX gene family has been got more attention from the scientific community in the past couple of years. The genome-wide identification analysis of BBX genes has been already investigated in rice [14] and other important plants such as Arabidopsis , tomato, potato, pear and apple [1, 14, 3336]. In this study, we also reported the genome-wide identification of BBX genes in five Poaceae species (maize, rice, sorghum, millet, and stiff brome), and their expression analysis under abiotic (cold, drought and salt), hormones (GA, ABA, SA and MeJA) and metal stresses (Cr, Cd, Ni and Fe) in rice.…”
Section: Discussionmentioning
confidence: 99%